Closing the Gap: Supporting Patients' Transition to Self-Management after Hospitalization - Pollack, Ari H; Backonja, Uba; Miller, Andrew D; Mishra, Sonali R; Khelifi, Maher; Kendall, Logan; Pratt, Wanda (Proceedings of the SIGCHI conference on human factors in computing systems. CHI Conference, 2016)
Patients going home after a hospitalization face many challenges. This transition period exposes patients to unnecessary risks related to inadequate preparation prior to leaving the hospital, potentially leading to errors and patient harm. Although patients engaging in self-management have better health outcomes and increased self-efficacy, little is known about the processes in place to support and develop these skills for patients leaving the hospital. Through qualitative interviews and observations of 28 patients during and after their hospitalizations, we explore the challenges they face transitioning from hospital care to self-management. We identify three key elements in this process: knowledge, resources, and self-efficacy. We describe how both system and individual factors contribute to breakdowns leading to ineffective patient management. This work expands our understanding of the unique challenges faced by patients during this difficult transition and uncovers important design opportunities for supporting crucial yet unmet patient needs.